2009
DOI: 10.1136/gut.2009.185074
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and geographical origin: major predictors of liver fibrosis and response to peginterferon and ribavirin in HCV-4

Abstract: Insulin resistance and geographical origin are major predictors of liver fibrosis and response to peginterferon and ribavirin in HCV-4 patients. Insulin resistance is frequently encountered in these patients, and correlated independently with serum HCV-RNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 33 publications
(43 reference statements)
7
60
2
Order By: Relevance
“…Mutations in the NS5A region, particularly in patients with more than 6 aa mutations in the Interferon RBV resistance determining region (IRRDR) are highly associated with good response to PEGIFN and RBV combination therapy, while a less diverse (≤ 5) IRRDR sequence is associated with nonresponse [144146] . Another predictor of response to PEGIFN/RBV therapy was found to be insulin resistance, which impairs response rates to PEG IFN/RBV therapy in HCV GT4 patients, and patients with Homeostasis Model Assessment for Insulin Resistance scores > 2 had lower SVR rates than those with scores < 2 (36% vs 72%) [147] . AbuMouch et al [148] found that adding vitaminD to the standard of care with PEGIFN/RBV therapy for HCVGT1 infected patients increases SVR rates from 42% to 82%.…”
Section: Background In Hcv Treatmentmentioning
confidence: 99%
“…Mutations in the NS5A region, particularly in patients with more than 6 aa mutations in the Interferon RBV resistance determining region (IRRDR) are highly associated with good response to PEGIFN and RBV combination therapy, while a less diverse (≤ 5) IRRDR sequence is associated with nonresponse [144146] . Another predictor of response to PEGIFN/RBV therapy was found to be insulin resistance, which impairs response rates to PEG IFN/RBV therapy in HCV GT4 patients, and patients with Homeostasis Model Assessment for Insulin Resistance scores > 2 had lower SVR rates than those with scores < 2 (36% vs 72%) [147] . AbuMouch et al [148] found that adding vitaminD to the standard of care with PEGIFN/RBV therapy for HCVGT1 infected patients increases SVR rates from 42% to 82%.…”
Section: Background In Hcv Treatmentmentioning
confidence: 99%
“…SOCS-7 mRNA expression is independent of signal transducer and activator of transcription 3 and is modulated by peroxisome proliferator-activated receptor gamma activity (Figure 1) [52,55] . HCV genotype 4 is the most common variant in the Middle East and Africa and is increasing in prevalence in Western countries [56] . Infection with HCV genotype 4 is associated with a high prevalence of hepatic steatosis and obesity; however, the impact of adiponectin on insulin resistance remains controversial [57,58] and specific mechanisms of insulin resistance in HCV genotype 4 infection also remain unclear.…”
Section: Pathogenesis Of Insulin Resistance In Patients With Chronic mentioning
confidence: 99%
“…Besides presence of advanced fibrosis, treatment outcome in genotype 4 has been associated with insulin resistance, hepatic steatosis and adiponectin changes, as in other genotypes [27][28][29][30][31][32]. Even though neither insulin resistance nor adiponectin levels were addressed in our study, indirect evidence, estimated by histologic presence of hepatic steatosis and measurement of BMI, showed that these factors were probably not related to genotype's 4 worse prognosis.…”
Section: Discussionmentioning
confidence: 45%